Religion and fight for social justice in the american political thought: richard rorty, john rawls, and martin luther king, jr. (2013)
John Rawls's "political" conception remains our most influential notion of justice designed to respect the irreducible and irreconcilable diversity of moral, philosophical, and religious doctrines characteristic of a pluralistic democratic culture. While we know from recent posthumous publications of Rawls's deep understanding of religion's ultimate importance, this conception seems to exclude a fundamental dimension of the most important struggles for social justice, like the role of the black church for Martin Luther King, Jr. and the civil rights movement. This article examines the later work of Richard Rorty for its potential in thinking through this tension surrounding religion and social justice and argues that by distinguishing appeals to transcendental authority within democratic discourse from the work of local parishes and spiritual communities, Rorty offers a way of understanding the role of religion in a pluralistic democratic culture capable of advancing the struggle for social justice consistent with the legacy of King and providing resources for Rawlsian liberals.